2014
DOI: 10.1016/j.jpainsymman.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Improve Communication Between Clinicians and Patients With Advanced Heart Failure: Methods and Challenges Behind the Working to Improve Discussions About Defibrillator Management Trial

Abstract: We report the challenges of the Working to Improve diScussions about DefibrillatOr Management (WISDOM) Trial, our novel, multicenter trial aimed at improving communication between cardiology clinicians and their patients with advanced heart failure (HF) who have implantable cardioverter defibrillators (ICDs). The study objectives are to: 1) increase ICD deactivation conversations; 2) increase the number of ICDs deactivated; and 3) improve psychological outcomes in bereaved caregivers. The unit of randomization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…While previous studies have examined the symptom experience from an HF perspective (8,10) and reported interventions to address palliative care communication gaps (14,29,30), a persistent gap has been the lack of randomized, controlled trials demonstrating the effectiveness of interventions that target the intersection of advanced HF and palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have examined the symptom experience from an HF perspective (8,10) and reported interventions to address palliative care communication gaps (14,29,30), a persistent gap has been the lack of randomized, controlled trials demonstrating the effectiveness of interventions that target the intersection of advanced HF and palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, comprehensive advance care planning should be a dynamic, iterative process rather than a singular event in time. A clinical trial is in progress exploring how to improve such communication between clinicians and ICD patients [NCT01459744] …”
Section: Determining Goals Of Carementioning
confidence: 99%
“…Trials such as the WISDOM trial aim to improve communication between the provider and the patient/caregiver with the goal of increasing conversations about deactivating ICDs, increasing ICD deactivations at the end of life, and improving psychological outcomes of bereaved caregivers. 25 The challenge with communication interventions is convincing clinicians that they need to improve their communication skills. In particular, many clinicians already believe that they are doing shared decision making.…”
Section: The Clinical/applied Research Of Decision Making – T2mentioning
confidence: 99%